CALCULATION OF DYNAMIC LOADS IN METAL STRUCTURES OF CRANE BOOM - Горбатюк, Євгеній (SWorldJournal, 2026)
To ensure trouble-free operation and increase the reliability of cranes in the calculations of structures and components of their working equipment, it is important to take into account dynamic loads that are several times higher than static loads. Eleme